Clinical Significance of Colonic Diverticulosis Associated with Bowel Symptoms and Colon Polyp - Lee, Kang-Moon (The Korean Academy of Medical Sciences, 2010)
This study was done to evaluate prospectively the clinical significance of colonic diverticulosis. In the 1,030 consecutive outpatients undergoing colonoscopy, the information on the demographics, the patterns of bowel symptoms, and the prevalence of colon polyp were analyzed according to the presence of colonic diverticulosis. The mean age of 1,030 patients were 52.2 yr and 59.3% were male. The prevalence of diverticulosis was 19.7% (203/1,030). Of 203 diverticulosis patients 85.2% were in proximal group, 5.4% in distal group and 9.4% in both group. Six (3.0%) patients were found to have diverticulitis. Multivariate logistic regression analysis showed that an old age, diabetes and the presence of polyp were significant factors associated with proximal or both diverticulosis. A significant difference was demonstrated between the patients of distal diverticular group and the controls for the symptom frequency scores within the previous 4 weeks. The items, which showed difference, were hard stool, urgency, flatus, chest discomfort and frequent urination. In conclusion, old age, diabetes and the presence of colon polyp were associated with proximal diverticulosis. The temporal symptoms were more frequent in distal diverticulosis than in proximal diverticulosis in the study subjects.